Comparing three scheduling methods using BIM models in the Last Planner System - Brioso, X (2017)
This study was partially funded by the Dirección de Gestión de la Investigación at Pontifical Catholic University of Peru and the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica del Perú (CONCYTEC from its acronym in Spanish), according to the Convenio de Gestión N° 232-2015-FONDECYT. We would also like to thank to Dilmer Dueñas, who kindly participated as instructor in the workshops